The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0177429
|View full text |Cite
|
Sign up to set email alerts
|

Genetic rescue of an endangered domestic animal through outcrossing with closely related breeds: A case study of the Norwegian Lundehund

Abstract: Genetic rescue, outcrossing with individuals from a related population, is used to augment genetic diversity in populations threatened by severe inbreeding and extinction. The endangered Norwegian Lundehund dog underwent at least two severe bottlenecks in the 1940s and 1960s that each left only five inbred dogs, and the approximately 1500 dogs remaining world-wide today appear to descend from only two individuals. The Lundehund has a high prevalence of a gastrointestinal disease, to which all remaining dogs ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Inbreeding results in mutational load in populations that may negatively impact on population viability. 'Genetic rescue' of highly inbred populations may be possible by the introduction of genetically diverse individuals 71 ; however, rescuing genetic diversity in the Thoroughbred will be challenging due to the limitations of a closed stud book. Furthermore, the population has a small effective population size (N e ) and a limited numbers of stallions have had a disproportionate influence on the genetic composition of the Thoroughbred; 97% of pedigrees of the horses included here feature the ancestral sire, Northern Dancer (1961) and 35% and 55% of pedigrees in EUR and ANZ contain Sadler's Wells (1981) and Danehill (1986), respectively (S1 Text).…”
Section: Discussionmentioning
confidence: 99%
“…Inbreeding results in mutational load in populations that may negatively impact on population viability. 'Genetic rescue' of highly inbred populations may be possible by the introduction of genetically diverse individuals 71 ; however, rescuing genetic diversity in the Thoroughbred will be challenging due to the limitations of a closed stud book. Furthermore, the population has a small effective population size (N e ) and a limited numbers of stallions have had a disproportionate influence on the genetic composition of the Thoroughbred; 97% of pedigrees of the horses included here feature the ancestral sire, Northern Dancer (1961) and 35% and 55% of pedigrees in EUR and ANZ contain Sadler's Wells (1981) and Danehill (1986), respectively (S1 Text).…”
Section: Discussionmentioning
confidence: 99%
“…These parameters permit one heterozygote and five missing genotypes within windows of 5 Mb and 50 SNPs. To compare results from different methods to detect possible selection, we plotted the distribution of focal genes detected in outlier flanking regions and ROH across all autosomal chromosomes based on the approach in Stronen et al (), comparing Jutland versus Holstein cattle, and Jutland versus Western Norwegian Red‐polled cattle.…”
Section: Methodsmentioning
confidence: 99%
“…The reported MAF values also were consistent with the range found in literature [ 11 , 28 ]. Recently, Stronen et al [ 29 ] reported lower values of genetic diversity in the endangered Norwegian Lundehund (e.g. ) compared to three reference breeds.…”
Section: Main Textmentioning
confidence: 99%